A forensic evaluation of impalement injuries. (April 2018) - Byard, Roger W
Impalement injuries transfix a victim in an inescapable or helpless position. A study was undertaken at Forensic Science SA from 2002 to 2016 of all impalement deaths. There were six vehicle accidents (M:F=5:1; age 14–67 years, average age 38.5 years) involving impalements with a tree branch ( n =2; groin and chest), a metal pipe ( n =2; leg and head), a metal bridge railing (groin) and a metal fence post (chest). Two cases (both males, aged 47 and 18 years) had slipped on fences/gates, with impalements of the ankle and groin. A case of suicide (male, aged 80 years) was impaled through the head on a bolt fixed to the floor. A homicide case (male, aged 27 years) involved impalement through the chest by a spear from a spear gun. In certain cases (e.g. with anogenital injuries), differentiating accidental from inflicted impalement injuries may be difficult. In equivocal cases, adequate scene evaluations with photographic documentation are required prior to autopsy, ideally with the object available for examination.